Biofuels and Biochemicals Production - Thaddeus Ezeji (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The high demand and depletion of petroleum reserves and the associated impact on the environment, together with volatility in the energy market price over the past three decades, have led to tremendous efforts in bio-based research activities, especially in biofuels and biochemicals. Most people associate petroleum with gasoline, however, approximately 6000 petroleum-derived products are available on the market today. Ironically, these petroleum-derived products have not elicited a high level of interest among the populace and media due, in part, to little awareness of the origins of these important products. Given the finite nature of petroleum, it is critical to devote substantial amounts of energy and resources on the development of renewable chemicals, as is currently done for fuels. Theoretically, the bioproduction of gasoline-like fuels and the 6000 petroleum-derived products are within the realm of possibility since our aquatic and terrestrial ecosystems contain abundant and diverse microorganisms capable of catalyzing unlimited numbers of reactions. Moreover, the fields of synthetic biology and metabolic engineering have evolved to the point that a wide range of microorganisms can be enticed or manipulated to catalyze foreign, or improve indigenous, biosynthetic reactions. To increase the concentration of products of interest and to ensure consistent productivity and yield, compatible fermentation processes must be used. Greater agricultural and chemical production during the past three decades, due in part to population increase and industrialization, has generated increasing levels of waste, which must be treated prior to discharge into waterways or wastewater treatment plants. Thus, in addition to the need to understand the physiology and metabolism of microbial catalysts of biotechnological significance, development of cost-effective fermentation strategies to produce biofuels and chemicals of interests while generating minimal waste, or better yet, converting waste into value-added products, is crucial. In this Special Issue, we invite authors to submit original research and review articles that increase our understanding of fermentation technology vis-à-vis production of liquid biofuels and biochemicals, and fermentation strategies that alleviate product toxicity to the fermenting microorganism while enhancing productivity. Further, original research articles and reviews focused on anaerobic digestion, production of gaseous biofuels, fermentation optimization using modelling and simulations, metabolic engineering, or development of tailor-made fermentation processes are welcome.